2001
DOI: 10.1046/j.1365-2842.2001.00727.x
|View full text |Cite
|
Sign up to set email alerts
|

Pain measurement in TMD patients: evaluation of precision and sensitivity of different scales

Abstract: The aim of this study was to evaluate the precision and sensitivity of four different pain rating scales in 59 temporomandibular disorders (TMD) patients. The capacity of describing changes in symptoms during treatment was also addressed. All patients were asked to answer four pain scales: Visual Analogue Scale (VAS), Numerical Scale (NS), Behaviour Rating Scale (BRS) and Verbal Scale (VS). Two measurements were taken before any treatment. After beginning it, follow-ups and repeated measurements were taken 1 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
16

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 28 publications
0
57
0
16
Order By: Relevance
“…The VAS was a 100-mm line in which the patient recorded pain intensity by marking a point on the line between the two extremes where the left extreme of the scale is marked "no pain" and the right one is marked "the worst imaginable pain". VAS is a simple, efficient, reliable and valid method to measure pain intensity and is extensively used in clinical settings and researches 18,19 . PPT was measured using a pressure digital algometer with a 1 cm 2 flat-circular shape tip at one end (Kratos ® Equipamentos Industriais).…”
Section: Methodsmentioning
confidence: 99%
“…The VAS was a 100-mm line in which the patient recorded pain intensity by marking a point on the line between the two extremes where the left extreme of the scale is marked "no pain" and the right one is marked "the worst imaginable pain". VAS is a simple, efficient, reliable and valid method to measure pain intensity and is extensively used in clinical settings and researches 18,19 . PPT was measured using a pressure digital algometer with a 1 cm 2 flat-circular shape tip at one end (Kratos ® Equipamentos Industriais).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, all included participants were asked to report specific characteristics regarding their jaw problem (eg, onset, duration of symptoms, treatments received) and their intensity of pain in the jaw (VAS score) 49,[55][56][57][58] and to complete the Neck Disability Index (NDI), 59,60 the JFS, 61 and a questionnaire for history of jaw pain used by the RDC/TMD. 45 In addition, participants were asked to complete the Chronic Pain Grade Disability Questionnaire for TMD used by the RDC/TMD to evaluate the level of chronic disability due to TMDs.…”
Section: Methodsmentioning
confidence: 99%
“…However, an accurate diagnosis, elimination of contributing factors, necessary pharmacotherapeutics, physical therapy and patient compliance can lead to successful management. Conti et al 4 have demonstrated a decrease of about 50% in pain severity of chronic TMD patients, in spite of the type of pain measurement or type of treatment.…”
Section: Treatmentmentioning
confidence: 99%